Is Intestinal Dysbiosis-Associated With Immunosuppressive Therapy a Key Factor in the Pathophysiology of Post-Transplant Diabetes Mellitus? - Faucher, Quentin; Jardou, Manon; Brossier, Clarisse; Picard, Nicolas; Marquet, Pierre; Lawson, Roland (Frontiers in Endocrinology, 2022)
Post-transplant diabetes mellitus (PTDM) is one of the most common and deleterious comorbidities after solid organ transplantation (SOT). Its incidence varies depending on the organs transplanted and can affect up to 40% of patients. Current research indicates that PTDM shares several common features with type 2 diabetes mellitus (T2DM) in non-transplant populations. However, the pathophysiology of PTDM is still poorly characterized. Therefore, ways should be sought to improve its diagnosis and therapeutic management. A clear correlation has been made between PTDM and the use of immunosuppressants. Moreover, immunosuppressants are known to induce gut microbiota alterations, also called intestinal dysbiosis. Whereas the role of intestinal dysbiosis in the development of T2DM has been well documented, little is known about its impacts on PTDM. Functional alterations associated with intestinal dysbiosis, especially defects in pathways generating physiologically active bacterial metabolites (e.g., short-chain fatty acids, trimethylamine N-oxide, indole and kynurenine) are known to favour several metabolic disorders. This publication aims at discussing the potential role of intestinal dysbiosis and dysregulation of bacterial metabolites associated with immunosuppressive therapy in the occurrence of PTDM.